STUDENTS' RESPONSES TOWARD WRITING GREETING CARDS USING CANVA THROUGH PROJECT-BASED LEARNING - Yana Yana; Milenia Dwi Agustin (IKIP Siliwangi, 2024)
The goal of this study is to see how students react to creating greeting cards with Canva through project-based learning. Canva allows pupils to expand their creativity and ideas for expressing things in writing. The sample for this study was eighth-grade junior high school students in Padalarang, and the research technique was descriptive qualitative. The research tools were obtained using a ten-questions of the questionnaire. The researcher found that students' responses to producing greeting cards using Canva through project-based learning were favourable based on the results of the data analysis. This response demonstrates that canva can be used effectively in writing. Based on the data, 70% of respondents properly characterize text using Canva as part of project-based learning. Using Canva, 60% of pupils can improve their creativity in explaining things. However, 50% of students have yet to understand Canva's capabilities, making it difficult to create greeting cards quickly. Furthermore, in this pandemic circumstance, employing online learning may be diverse media in the teaching and learning process. Canva may be used as a substitute for writing greeting cards. Using Canva, students find it enjoyable and straightforward to create greeting cards.